Life History of Thalerosphyrus (Ephemeroptera: Heptageniidae) in Tropical Rivers with Reference to the Varying Altitude - Suhaila Ab. Hamid; Che Salmah Md Raw; Abu Hassan Ahmad (Tropical Life Sciences Research, 2016)
The life history and the influence of environmental parameters on Thalerosphyrus were investigated in two first-order rivers—the Batu Hampar River and the Teroi River of Gunung Jerai, Kedah—in northern peninsular Malaysia. Based on nymphal body length, Thalerosphyrus was found to be trivoltine in both rivers, regardless of the altitudinal difference, but its population abundance was four times higher in the Teroi River, presumably related to its better survival in the lower water temperature. At least nine instars of Thalerosphyrus were detected in the field-collected nymphs. Its life cycle was completed within 2.5–3.0 months, with overlapping cohorts and continual emergence of up to 3 months. The main driving factors of the high abundance of Thalerosphyrus were the water temperature and habitat quality. Kitar hayat dan pengaruh parameter persekitaran ke atas Thalerosphyrus telah dikaji di dua sungai order pertama; Sungai Batu Hampar dan Sungai Teroi dari Gunung Jerai, Kedah di utara Semenanjung Malaysia. Berdasarkan panjang badan nimfa, Thalerosphyrus didapati mempunyai kitar hidup trivoltin di kedua-dua sungai tanpa mengambil kira perbezaan altitud namun kelimpahan populasinya adalah empat kali ganda lebih tinggi di Sungai Teroi, berkemungkinan berkaitan dengan kemandirian hidup yang lebih baik dalam air yang bersuhu rendah. Sekurang-kurangnya sembilan instar Thalerosphyrus telah dikenalpasti daripada nimfa yang dikumpulkan dari lapangan. Kitaran hayatnya lengkap dalam tempoh 2.5–3.0 bulan dengan kohot bertindih dan kemunculan berterusan sehingga 3 bulan. Faktor utama yang menyumbang kepada kelimpahan Thalerosphyrus yang tinggi adalah suhu air dan kualiti habitat.